Inimizade racial e letalidade policial no Brasil - Moitinho, Victória Cruz (2023)
The present study is located in the field of Criminology and is inspired by decolonial studies to critically present the association between enemy and racism. Race doesn’t exist as a biological or genetic concept, but as a political and ideological factor mobilized to bring about differences between human groups, supporting discriminatory practices. It is based on race and, consequently, on racism, that a differentiation between subjects is forged, conceiving them as citizens or enemies, depending on the negative or positive meanings attributed to the group. At this point, the research aims to investigate the relationship between enmity and racism, through data produced by the Brazilian Public Security Forum (FBSP), between the years 2016 to 2021. That the main victims of formal control agencies are color people, indicating a racialization of death based on a warlike discourse. The figure of enmity, therefore, is not only an open penal clause, but is also determined by raciality, that is, by the idea that a group of people would be inferior, lacking the condition of being human, and could have its existence ceased at anytime. Because they lack the status of citizens, color people are assimilated as enemies, which is why they are overrepresented in the rates of deaths resulting from police intervention. Brazilian police officers reproduce a war discourse based on white fear and on the device of enmity, conceiving some subjects and groups as a threat to order and security. For this reason, the exercise of punitive power becomes lethal, and its interference is a consequence of structural racism. Therefore, in addition to news, documents and data produced by institutions and civil organizations, the investigation will make use of bibliography on racial issues, enmity and police activity. The conclusion is that in Brazil racial enmity persists, built through a historical and cultural discourse forged in race and continuously reproduced, which places blacks as the main enemy of the State.